2019
DOI: 10.4236/jacen.2019.82008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Use and Re-Use of Selected Vegetable Oils on the Proximate, Minerals, Mineral Ratios and Mineral Safety Index of Raw and Fried Plantain Chips: Note I

Abstract: Raw and fried plantain chips obtained from the use and re-use of olive, refined palm olein and coconut oils were investigated for the proximate, mineral compositions, computed mineral ratios and the mineral safety index using standard analytical methods. For the selected oils (both use and re-use): first and second re-use and the fresh plantain chips (unprocessed plantain chips; UPC) had the following range results: proximate composition (%)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Apart from Met and Cys, the AAS and CS of the essential amino acids in SDs were greater than 1 and 0.6, respectively, indicating that the EAA is relatively well-balanced, which could provide a high-quality, comprehensive protein. The EAAI is a quantitative indicator of how well the measured essential amino acid content matches the standard protein content, with a value less than 75 indicating that the food is an inadequate source of protein ( 39 ). Additionally, the EAAI is a quantitative parameter that quantifies the relationship between the measured basic AA content and the standard protein content.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from Met and Cys, the AAS and CS of the essential amino acids in SDs were greater than 1 and 0.6, respectively, indicating that the EAA is relatively well-balanced, which could provide a high-quality, comprehensive protein. The EAAI is a quantitative indicator of how well the measured essential amino acid content matches the standard protein content, with a value less than 75 indicating that the food is an inadequate source of protein ( 39 ). Additionally, the EAAI is a quantitative parameter that quantifies the relationship between the measured basic AA content and the standard protein content.…”
Section: Resultsmentioning
confidence: 99%
“…Throughout the world, plantain is a significant staple item and can be used to prepare food at all ripening stages, even when overripe [ 12 ]. Peels from plantains make up 30–40% of the overall weight of the fruit.…”
Section: Introductionmentioning
confidence: 99%
“…While the effect of chronic exposure to small amounts of some metals seems to be well understood, several incidents show the seriousness of high levels of exposure to some noxious metals, particularly Cd, Cr3+ and Pb [6]. The determination of metals in vegetable oils and fats has been under investigation for several years and is still a formidable problem [3,7,1]. Manjusha et al (2019) observed that the quality of edible oils is directly linked to the concentration of some trace metals.…”
Section: Introductionmentioning
confidence: 99%
“…According to Cindiric et al (2007) and Jamali et al (2008), the presence of metals in edible vegetable oils relies on many factors, which include: the soil, environment and genetic structure of the plant, as well as fertilizers and pesticides introduced during the production process or by contamination from the metal processing equipment or shipping containers. Also these metals could get into the edible oils through many food processing methods such as frying and baking [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation